Individual Behavior as a Defense in the "War on Cyberterror": A System Dynamics Approach. (1st February 2018) - Armenia, Stefano; Tsaples, Georgios
ABSTRACT: The problem of cyberterrorism, despite its contested nature, is an important area of research. Scholars agree that the most dangerous targets for such attacks are critical infrastructure and organizations that are vital to society due to their interconnectedness to the modern world and their increasing reliance on the cyber domain for their operations. Thus, their security and protection against cyberterrorism is of elevated importance. Given the lack of documented cases of cyberterrorism, the purpose of this article is to simulate the threat of a terrorist act on a critical infrastructure, using a computer virus and to investigate how the individual behavior of employees affects security.